Penerapan Metode Analytical Hierarchy Process Untuk Seleksi Usaha Penangkapan Ikan Komoditas Unggulan - Husain, Hariati; Citra Yustitya Gobel; Misrawati Aprilyana Puspa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The superior commodity fishing business assistance program is one of the Maritime Affairs and Fisheries Service programs aimed at fishermen in the Gorontalo area. Gorontalo Province has abundant marine resources, the fisheries sector plays a vital role in the regional economy and community welfare. However, fishing businesses often face various challenges, such as fish stock fluctuations, climate change, overfishing, and environmental impacts. Therefore, selecting superior commodities in the fishing business is crucial to ensure the sustainability of marine resources and optimal economic benefits. This research aims to apply the Analytical Hierarchy Process Method in selecting superior commodity fishing businesses in Indonesia. By identifying and evaluating various relevant criteria, it is hoped that this research can provide appropriate and sustainable recommendations for stakeholders in the fisheries sector. The results of testing the application of the AHP method in determining the selection of fishermen's fishing business on behalf of the senses with the alternative Fair on the Criteria for Receiving Assistance, the Alternative Good on the Equipment Ownership Criteria, the Alternative Good on the Criteria of Operational Skills and Total Income obtained a calculation result of 0.7648 > the Size Value namely 0.60, with the conclusion that these fishermen can be accepted as recipients of fishing business assistance. Based on the research results, it can be concluded that the application of the Analytical Hierarchy Process (AHP) method for fishing business selection has proven effective in assisting complex decision making involving various criteria and sub-criteria